Pharmacokinetics of Sustained-Release and Transdermal Buprenorphine in Göttingen Minipigs (Sus scrofa domestica) - Thiede, Allison J (J Am Assoc Lab Anim Sci, 2014)
The opioid buprenorphine has been shown to provide adequate postoperative analgesia in both companion and laboratory animals. However, its use is still hindered by the need for multiple parenteral injections to achieve continuous analgesia. The purpose of the current study was to conduct a pharmacokinetic analysis of 2 new long-acting formulations of buprenorphine—an injectable sustained-release buprenorphine (SRB) and a transdermal buprenorphine (TDB) patch—in healthy Göttingen minipigs by using liquid chromatography–electrospray ionization–tandem mass spectrometry. Administration of 0.18 mg/kg SC SRB and 30 μg/h TDB achieved AUC(0-Tlast) of 221.6 ± 26.8 and 25.2 ± 3.9 ng × h/mL, respectively, compared with 9.7 ± 1.4 ng*h/mL for 0.02 mg/kg IV buprenorphine. By using a hypothesized therapeutic plasma buprenorphine concentration threshold of 0.1 ng/mL, therapeutic concentrations were achieved at the first study time point (5 to 30 min) and lasted an average of 8.0 ± 1.3 h for intravenous buprenorphine and 264.0 ± 32.2 h for SRB. TDB achieved therapeutic concentrations in 12 to 24 h after patch application, which lasted until the patch was removed at 72 h. The results of this study suggest that SRB and TDB are long-acting alternatives for pain management, and their use could decrease animal handling and stress, thereby simplifying pain management and improving welfare in laboratory swine.